Transformation of one-dimensional silicon photonic crystal into Fabry-Perot resonator - PEROVA, TATIANA (My University, 2011)
The model of transformation of one-dimensional, high-contrast silicon photonic crystal (PC) into a Fabry-Perot resonator is considered. This transformation is achieved either by decreasing the number of periods up to 1.5 or the introduction of optical defect in the ordinary multi-period PC while retaining a high modulation of the resonance peaks up to ~0.95. The simultaneous use of maps of photonic band gaps (PBG) and transmission bands can predict the appearance or disappearance of PBGs in the optical spectra as well as to determine their position and width depending on the order of the band-gap (or stop-band) and the value of the filling fraction. The variation of the refractive index by 0.2 results in significant shift of the resonance peaks of high order up to 10% of the frequency corresponding to the center of the peak.
Proceedings SPIE
Photonics West
PUBLISHED
Keywords: Optics